Optimization and application of parameter identification error algorithm for steam turbine governing system. Issue 1 (1st December 2022) - Zhu, Longfei; Si, Paiyou; Liu, Shuangbai; Mei, Long; Xie, Changya; Zhang, Teng; Hu, Yuou
Abstract: The parameter identification of the steam turbine speed governing system needs to be realized by the fitting of the measured response curve of the steam turbine active power. The national standard puts forward strict requirements on the error of the identification result. At present, error calculation is often realized by manual punctuation, which is a complicated process and greatly influenced by human judgment. Hence it needs to be improved urgently. In this paper, polynomial fitting and improved sliding window method are used to optimize the error identification algorithm of the steam turbine active power response curve. The visualization of the program is realized based on the Python language. The algorithm improves the data processing efficiency and reduces the influence of human judgment. The calculation results meet the standard requirements.